Transformasi Kreativitas Siswa melalui Pelatihan Jurnalistik: Mengembangkan Literasi Digital di SMAN 1 Samaturu - Nasir, Agus; Yasir, Muhammad; Rahayu, Ayu; Arma Wangsa; Sarah Alvia (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Adapting to rapidly evolving technology and honing digital literacy is a necessity for students at SMAN 1 Samaturu to ensure they do not fall behind in an increasingly digital world. However, the challenge lies in the lack of digital journalism literacy programs, despite the significant potential of this field to enhance general literacy and provide practical skills for students. The limited availability of journalism training, such as writing articles, conducting interviews, and managing school media, reduces students' opportunities to learn in this area. To address this, a digital journalism training was held on August 13, 2024, with 50 students participating. The activity included planning, training, and evaluation stages. As a result, students were able to recognize their potential in journalism. They not only learned to write and edit articles but also developed the ability to understand, analyze, and process information critically. They became more sensitive to accurate information sources, understood good narrative structures, and improved their communication skills, thus enhancing their digital literacy.